The Influence of Smartphone Use on Tweens' Capacity for Complex Critical Thinking - Rosa Angela Fabio; Rossella Suriano (MDPI AG, 2023)
The spread of modern technologies exposes many people to a high level of ambiguous and misleading information that can impact people's judgments and worldviews. This happens especially in a phase of life such as preadolescence when children are particularly sensitive to external conditioning. Critical thinking can be seen as the first line of defense against misleading information. However, little is known about the consequences of media use on the critical thinking skills of tweens. In this study, we evaluated the effects of problematic smartphone use on the various stages of critical thinking, comparing high and low tween smartphone users. The results confirm the main hypothesis, namely, that problematic smartphone use is related to the ability to think critically. There was a significant difference between high and low users in the third phase of critical thinking: evaluation of sources.